1980
DOI: 10.1084/jem.151.3.573
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of receptor binding proteins and immunogens of virulent Treponema pallidum.

Abstract: Receptor binding proteins of Treponema pallidum were identified by incubation of [35S]methionine-labeled, soluble T. pallidum preparations with formaldehyde-fixed HEp-2 cells. Three major treponemal proteins (bands 1--3) that avidly bound to the eucaryotic cell surface were detected by sodium dodecylsulfate-polyacrylamide gel electrophoresis and fluorography. Brief trypsin treatment of HEp-2 cells before formaldehyde fixation reduced the extent of the interaction of these treponemal macromolecules, which impli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
80
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 29 publications
7
80
0
Order By: Relevance
“…Several cytadhesins have been identified by mild extraction of pathogenic bacteria with nonionic detergents such as OGP, by using formaldehyde-or glutaraldehyde-fixed host cell cultures (7)(8)(9). Formaldehyde-fixed mouse L cells have been used to study the adherence of Chlamydia psittaci (11).…”
Section: Discussionmentioning
confidence: 99%
“…Several cytadhesins have been identified by mild extraction of pathogenic bacteria with nonionic detergents such as OGP, by using formaldehyde-or glutaraldehyde-fixed host cell cultures (7)(8)(9). Formaldehyde-fixed mouse L cells have been used to study the adherence of Chlamydia psittaci (11).…”
Section: Discussionmentioning
confidence: 99%
“…Three treponemal proteins with fibronectin-binding properties were discovered and partially characterized over 20 years ago (18,310), but until recently the identity of potential T. pallidum adhesins was unknown. Cameron et al (41) used computer analysis to search the T. pallidum genome for adhesin candidates.…”
Section: Attachmentmentioning
confidence: 99%
“…Although it is now 13 years since the publication of the Nichols strain complete genome sequence (24) and over 30 years since initial binding studies demonstrated that T. pallidum is capable of adhering to mammalian cells (3,21,30) and components of the extracellular matrix (ECM) (23,70), data regarding the molecular basis of these important pathogenic interactions have only recently begun to emerge. Previously, our laboratory identified the T. pallidum adhesin Tp0751 and demonstrated that this adhesin binds specifically to a variety of laminin isoforms, which are abundant glycoprotein components of the basement membrane that underlie endothelial cell layers, in a dose-dependent manner (8,9).…”
mentioning
confidence: 99%